2021
DOI: 10.2967/jnmt.121.262462
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Correlation Between68Ga-PSMA-11 Renal PET Parameters and Renal Function Tests

Abstract: Ga-prostate-specific membrane antigen (PSMA) ligands are used for prostate cancer but also show high renal cortical uptake. In this study, we aimed to assess whether there is any correlation between renal PSMA PET parameters and renal function tests using the images of prostate cancer patients. Methods: 68 Ga-PSMA-11 PET/CT images of the patients with prostate cancer were retrospectively evaluated. The following PET parameters were obtained: SUV max , SUV mean , SUV max corrected for lean body weight, SUV mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Schierz and colleagues found that renal segmentation volume, as well as the renal SUV mean ‐to‐blood pool SUV mean ratio, and the renal SUV mean ‐to‐liver SUV mean ratio, correlated with MDRD eGFR in a study of 25 patients undergoing [ 68 Ga]Ga‐PSMA‐11 PET (Schierz et al, 2021 ). To the best of our knowledge, the present study is the first to demonstrate a correlation between [ 18 F]PSMA‐1007 PET parameters and eGFR, and it included a considerably larger study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schierz and colleagues found that renal segmentation volume, as well as the renal SUV mean ‐to‐blood pool SUV mean ratio, and the renal SUV mean ‐to‐liver SUV mean ratio, correlated with MDRD eGFR in a study of 25 patients undergoing [ 68 Ga]Ga‐PSMA‐11 PET (Schierz et al, 2021 ). To the best of our knowledge, the present study is the first to demonstrate a correlation between [ 18 F]PSMA‐1007 PET parameters and eGFR, and it included a considerably larger study population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on 25 patients found correlations between [ 68 Ga]Ga‐PSMA‐11 PET parameters and estimated GFR (eGFR), with two patients excluded due to high activity in renal calyces (Schierz et al, 2021 ). [ 18 F]PSMA‐1007 has significantly lower urinary excretion than [ 68 Ga]Ga‐PSMA‐11 (Afshar‐Oromieh et al, 2016 ; Giesel et al, 2017 ), making renal uptake easier to distinguish, and thus, potentially making it more suitable for quantification and imaging and of renal cortical function.…”
Section: Introductionmentioning
confidence: 99%
“…PSMA is physiologically overexpressed in the proximal tubular cells of the kidneys and 68 Ga-PSMA is excreted via the renal system [ 24 ]. Several studies have shown the utility of PSMA in the imaging of renal function [ 25 , 26 , 27 , 28 ]; therefore, we hypothesised that 68 Ga-PSMA PET/CT imaging could be used as a surrogate for the determination of PSMA-PETderived split renal function (SRF) at baseline, to assess kidney function and detect changes during follow-up, and to rule out obstruction induced by tumour or renal dysfunction caused by PSMA-targeted radioligand treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 68 Ga]Ga-PSMA-11 PET has been compared to technetium-99m labeled dimercaptosuccinic acid (DMSA) scan in two adult patients with pyelonephritis [ 6 , 7 ]. A recent study has shown correlation between renal uptake of [ 68 Ga]Ga-PSMA-11 and renal function as measured with glomerular filtration rate (GFR) [ 8 ]. A comparison of split renal function using technetium-99m labeled mercaptotriglycene ([ 99m Tc]Tc-MAG3) renography and [ 68 Ga]Ga-PSMA-11 PET has shown reasonable agreement between the modalities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%